A Generalized Algorithm for the Generation of Correlated Rayleigh Fading Envelopes in Wireless Channels. Issue 5 (12th December 2005) - Tran, Le Chung; Wysocki, Tadeusz A.; Mertins, Alfred; Seberry, Jennifer
Abstract : Although generation of correlated Rayleigh fading envelopes has been intensively considered in the literature, all conventional methods have their own shortcomings, which seriously impede their applicability. A very general, straightforward algorithm for the generation of an arbitrary number of Rayleigh envelopes with any desired, equal or unequal power, in wireless channels either with or without Doppler frequency shifts, is proposed. The proposed algorithm can be applied to the case of spatial correlation, such as with multiple antennas in multiple-input multiple-output (MIMO) systems, or spectral correlation between the random processes like in orthogonal frequency-division multiplexing (OFDM) systems. It can also be used for generating correlated Rayleigh fading envelopes in either discrete-time instants or a real-time scenario . Besides being more generalized, our proposed algorithm is more precise, while overcoming all shortcomings of the conventional methods.